WADY WRODZONEShort-term results of neonatal arterial switch operation for simple and complex transposition of the great arteries. A single centre experience - Wojtalik, Michał; Sologashvili, Tornike; Mrówczyński, Wojciech; Mroziński, Bartłomiej; Ładziński, Piotr; Wodziński, Andrzej; Westerski, Przemysław; Bartkowska-Śniatkowska, Alicja; Henschke, Jacek; Bartkowski, Rafał (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce: In 1975 Jaten and colleagues described the first successful arterial switch operation (ASO) for transposition of the great arteries (TGA), and practised it for more than thirty years. The ASO has become the treatment of choice in many centres. The purpose of this study was to assess short-term results after neonatal ASO. Aim: The aim of this study was to assess early and mid-term results of ASO in a single centre. Material and Methods: Between December 1997 and June 2009 at our centre 150 ASO were performed by one surgeon. Patients’ charts, surgical reports and echocardiograms were retrospectively reviewed. Patients were divided into three groups according to years – first 4 years, second 4 years, and third 4 years – and each group was divided into two subgroups A and B, subgroup A consisting of simple TGA with intact ventricular septum (IVS), and subgroup B consisting of patients with complex heart defects: TGA with ventricular septal defect (VSD), TGA with hypoplastic aortic arch or coarctation of aorta and Taussig-Bing heart. Group I consisted of 54 patients, group II 38, and group III 58. Results: Our study shows that 30-day mortality was higher in the first group. It is also noticeable that complex TGA confer elevated risk for early mortality. Coronary artery anatomy was not identified as a risk factor. Conclusions: Despite risks, the study shows that neonatal ASO can be performed with acceptable morbidity and mortality even in patients with complex heart defects.